The prognostic value of pretreatment neutrophil-to-lymphocyte ratio in breast cancer: Deleterious or advantageous? - Qingqing Ou; Jiang Cheng; Licui Zhang; Huimin Wang; Wei Wang; Yajing Ma (Tumor Biology, 2017)
Breast cancer is one of the leading malignant tumors that endanger women’s health worldwide. Despite the rapid progress on the therapies, including chemotherapy, surgical resection, and other auxiliary methods, there were still numerous people died of breast cancer, which promoted the researchers to concentrate on the prognostic factor of breast cancer. In recent years, an increasing number of studies have been focused on the prognostic value of pretreatment neutrophil-to-lymphocyte ratio in breast cancer. This article is a brief review of the associations between neutrophil-to-lymphocyte ratio and the prognosis of breast cancer patients, which may give a greater insight into the development of breast cancer and enable clinicians to cure it completely.